Neutrophil elastase as a versatile cleavage enzyme for activation of αvβ3 integrin-targeted small molecule drug conjugates with different payload classes in the tumor microenvironment - Rebstock, Anne-Sophie; Wiedmann, Mareike; Stelte-Ludwig, Beatrix; Wong, Harvey; Johnson, Amy J.; Izumi, Raquel; Hamdy, Ahmed; Lerchen, Hans-Georg (Frontiers in Pharmacology, 2024)
The development of bioconjugates for the targeted delivery of anticancer agents is gaining momentum after recent success of antibody drug conjugates (ADCs) in the clinic. Smaller format conjugates may have several advantages including better tumor penetration; however, cellular uptake and trafficking may be substantially different from ADCs. To fully leverage the potential of small molecule drug conjugates (SMDCs) with potent binding molecules mediating tumor homing, novel linker chemistries susceptible for efficient extracellular activation and payload release in the tumor microenvironment (TME) need to be explored. Towards this goal, we designed a novel class of SMDCs, which target αvβ3 integrins for tumor homing and are cleaved by neutrophil elastase (NE), a serine protease active in the TME. A peptidomimetic αvβ3 ligand was attached via optimized linkers composed of substrate peptide sequences of NE connected to different functional groups of various payload classes, such as camptothecins, monomethyl auristatin E, kinesin spindle protein inhibitors (KSPi) and cyclin-dependent kinase 9 inhibitors (CDK-9i). Surprisingly, NE-mediated cleavage was found compatible with the diverse linker attachments via hindered ester bonds, amide bonds and sulfoximide bonds. Efficient and traceless release of the respective payloads was demonstrated in biochemical assays. The newly designed SMDCs were highly stable in buffer as well as in rat and human plasma. Cytotoxicity of the SMDCs in cancer cell lines was clearly dependent on NE. IC50 values were in the nanomolar or sub-nanomolar range across several cancer cell lines reaching similar potencies as compared to the respective payloads only in the presence of NE. In vivo pharmacokinetics evaluating SMDC and free payload exposures in rat and particularly the robust efficacy with good tolerability in triple negative breast and small cell lung cancer murine models demonstrate the utility of this approach for selective delivery of payloads to the tumor. These results also highlight the broad scope of potential payloads and suitable conjugation chemistries paving the way for future SMDCs harnessing the safety features of targeted delivery approaches in combination with NE cleavage in the TME.